2018
DOI: 10.1002/pd.5232
|View full text |Cite
|
Sign up to set email alerts
|

Early hemodynamic changes after fetal aortic stenosis valvuloplasty predict biventricular circulation at birth

Abstract: Technically successful FAV is associated with immediate improvements in left heart physiology that are predictive of BiV circulation at neonatal discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…A study by Selamet Tierney et al in 2007 described the 5/6 area‐length method technique to compute ventricular volumes but did not provide a reference data set for healthy fetuses throughout gestation. This method was used by the same group in a recent publication for assessing ventricular volume but did not provide or reference normal data for comparison with our study . The pulsed Doppler assessment of right and LV CO was first reported by Rizzo and Arduini in 1991, followed by articles by Mielke and Benda in 2001 and Kiserud et al in 2006.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A study by Selamet Tierney et al in 2007 described the 5/6 area‐length method technique to compute ventricular volumes but did not provide a reference data set for healthy fetuses throughout gestation. This method was used by the same group in a recent publication for assessing ventricular volume but did not provide or reference normal data for comparison with our study . The pulsed Doppler assessment of right and LV CO was first reported by Rizzo and Arduini in 1991, followed by articles by Mielke and Benda in 2001 and Kiserud et al in 2006.…”
Section: Discussionmentioning
confidence: 92%
“…Other techniques that have been described to compute the EDV and ESV are the 5/6 area‐length method and pulsed Doppler measurements of the velocity time integral and aortic and pulmonary annular diameters . A study by Selamet Tierney et al in 2007 described the 5/6 area‐length method technique to compute ventricular volumes but did not provide a reference data set for healthy fetuses throughout gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for only including isolated CHD were that altered neurodevelopment could otherwise be attributed to genetic or syndromic defects. Furthermore, cases with aortic valve stenosis that underwent fetal balloon valvuloplasty were excluded, since fetal brain oxygenation may have changed due to the intervention during pregnancy . Also, strictly minor cases (persistent left caval vein, mild pulmonary stenosis and restrictive foramen ovale) were also excluded, since in these cases, blood flow towards the brain is expected to be uncompromised.…”
Section: Methodsmentioning
confidence: 99%
“…In the more recent experience since 2009 (n = 71), probability of technical success (94%), fetal demise (4%), and biventricular circulation (66%) have all improved . Interestingly, recent analyses of our cohort have shown that specific echocardiographic changes, most powerfully anterograde aortic arch flow, within the first 24 hours following the procedure, can predict which cases will result in biventricular circulation in the newborn . Identifying immediate changes such as these are important in terms of counseling families about delivery planning and likely outcomes after birth …”
Section: Outcomes and Secondary Considerationsmentioning
confidence: 99%